THE ROLE OF TECHNOLOGY AND INNOVATION IN MARKETING TO GENERATION Z - Rahmat, Aldi; Hery Firdaos, Ikang; Faizal, Muhammad (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
This research aims to analyze and explain the role of technology and innovation in marketing to Generation Z in Sukabumi. The data of this study is MSMEs in Sukabumi City with a population of 31,926 and the sample used in this study is 100 business actors. web.raosoft.com The method in this study used quantitative research, with a data collection method, namely the distribution of questionnaires through Google Forms in the form of statements to respondents and interviews. The analysis method in this study explains that the role of technology and innovation has a positive and significant impact in increasing curiosity in Generation Z, with an impact of 61.2% while other variables influence 38.8%.